EVALUASI HASIL BELAJAR BEBERAPA MATERI PASSING BAWAH BOLAVOLI MENGGUNAKAN METODE WHOLE PRACTICE (STUDI PADA SISWA KELAS VIII SMP AL-ISLAM PEHNANGKA, NGAWI) - ABADI, FAUZAN (Jurnal Pendidikan Olahraga dan Kesehatan, 2014)
Abstract A lot of  learning methods that used for increasing student’s abilty to take control of volley ball under passing basic motion. However in fact, there is a lot of students who cannot take control this basic control yet with method which apllied by educators. Whole practice method is a learning way with presenting lesson entirely, step by step from general to spesific lesson which hopefuly can be repairing weaknesses of earlier educators. Kind of research that used by, is quasi-experimental with quantitative descriptive approach, using one group pretest-posttest design. The research is using population from all students of SMP AL-ISLAM Pehnangka, class VIII. Then about sampling, using a cluster random sampling method, is taking sample with group, not individualy. There is two ways to finding data,  manual statistic calculating and SPSS version 20.0 (Statistical Package for the Social Science). Taken from 5 time meeting, a whole samples who defined to knowing learning result from couple lessons of volley ball under passing with whole practice method. This research purpose is for evaluate learning result from couple lessons of volley ball under passing with whole practice method. Based on result of research, there is a conclusion appear and explain that learning using whole practice method was given great effect to learning result of volley ball under passing, in the mount of percentage, 13,37%. Keywords: Whole practice method, learning result and under passing